Clash of Champions Pada Ruangguru: Mendefinisikan Ulang Makna Prestasi Melalui Analisis Wacana Norman Fairclough - Wardani, Ayu; Afriani, Anindita Lintangdesi (DEPARTEMENT OF COMMUNICATION AND ISLAMIC BROADCASTING STUDIES, 2024)
This study discusses how the shifting meaning of achievement and the process of commodification is represented in the game show Clash of Champions organized by the technology-based education platform Ruangguru. Using Norman Fairclough's critical discourse analysis, this research explores the relationship between discursive, social, and textual practices within the show. The findings indicate that the competition positions achievement as a commodity aligned with global market needs, utilizing the accomplishments of finalist figures, such as Shakira and Axel, as marketing tools, in line with Mosco's framework of commodification. Critical discourse analysis also reveals that the meaning of achievement has shifted from being seen as the result of individual hard work to being perceived as excellence in specific fields, such as logic and mathematics, which hold market value. Moreover, the figure of runner-up Axel Giofanny reinforces the narrative that achievement is framed as success in obtaining scholarships and continuing education at prestigious universities abroad. This study contributes to understanding how technology-based education platforms reshape social values through the construction of competition and achievement discourse while reflecting the power of social structures in reproducing the ideology of global capitalism.